2012
DOI: 10.1093/jxb/ers186
|View full text |Cite
|
Sign up to set email alerts
|

The use of metabolomics integrated with transcriptomic and proteomic studies for identifying key steps involved in the control of nitrogen metabolism in crops such as maize

Abstract: Linking plant phenotype to gene and protein expression and also to metabolite synthesis and accumulation is one of the main challenges for improving agricultural production worldwide. Such a challenge is particularly relevant to crop nitrogen use efficiency (NUE). Here, the differences in leaf gene transcript, protein, and metabolite accumulation in maize subjected to long-term nitrogen (N)-deficient growth conditions at two important stages of plant development have been studied. The impact of N deficiency wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
145
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(163 citation statements)
references
References 103 publications
(114 reference statements)
15
145
3
Order By: Relevance
“…The rate of N uptake in roots is determined by ionic concentration (Tsay et al 2007 ), which is infl uenced by various stress conditions (Segonzac et al 2007 ). Recently, it was reported that in maize, N-defi ciency stress resembled the response of plants to a number of other biotic and abiotic stresses, in terms of transcript, protein, and metabolite accumulation (Amiour et al 2012 ). In rice, two proteins, fi brillin and hairpin-binding protein, have been identifi ed previously as N-defi ciency stressresponsive proteins (Song et al 2010 ;Amiour et al 2012 ).…”
Section: Nitrogen Starvation/limitationmentioning
confidence: 99%
“…The rate of N uptake in roots is determined by ionic concentration (Tsay et al 2007 ), which is infl uenced by various stress conditions (Segonzac et al 2007 ). Recently, it was reported that in maize, N-defi ciency stress resembled the response of plants to a number of other biotic and abiotic stresses, in terms of transcript, protein, and metabolite accumulation (Amiour et al 2012 ). In rice, two proteins, fi brillin and hairpin-binding protein, have been identifi ed previously as N-defi ciency stressresponsive proteins (Song et al 2010 ;Amiour et al 2012 ).…”
Section: Nitrogen Starvation/limitationmentioning
confidence: 99%
“…Thus, it would be possible for researchers to even predict the quantitative and qualitative efect an introduction or deduction that a selected element or compound could have in the gene network or pathway within a biological system. For example, it would be possible to predict what efect could high concentrations of Ca have on the phenotype or the production of a selected phenolic acid in a selected grain compartment (endosperm) [89]. The integration of these technologies would enable researchers to determine which gene region could be targeted to improve the levels of a desirable metabolite without afecting other biological systems.…”
Section: The Use Of -Omics Technologies To Improve Nutritional Bioavamentioning
confidence: 99%
“…79 Combinations of transcriptome, proteome and metabolite profiling helps in revealing the correlation between the expression of stress related biosynthetic genes and corresponding metabolic products, which further increases our understanding of plant stress responses. 83 discussed the potential use of 'Omics' studies to improve understanding of whole plant nitrogen econOmics in maize.…”
Section: Kusano Et Almentioning
confidence: 99%